HIGH FREQUENCY REGENERATION OF BACOPA MONNIERI PLANT CALLUS DERIVED FROM INTERNODE - B SUBASHRI; DR Y JUSTIN KOILPILLAI (International Journal of Pharma and Bio Sciences, 2013)
Bacopa Monnieri is an important medicinal plant belonging to the family Scrophulariaceae. Plant regeneration was achieved from internode. High frequency regeneration of callus was achieved from internodes inoculated on MS medium supplemented with Kinetin and 2, 4, D at 7µM concentration each. Primary shoot was induced from this callus in the medium containing. 0.1 kinetin and 1mg/l 2, 4, D. In vitro plantlets were successfully established with ex vitro.